Perancangan Quality Metric Untuk Control Quality Pada Proyek Sttf Ii Dago Giri Ii Menggunakan Metode Internal Control (studi Kasus Pt. Xyz) - Widigdo Adhy Utomo; Ika Arum Puspita; Achmad Fuad Bay (eProceedings of Engineering, 2020)
Abstrak PT. XYZ memiliki proyek pembangunan STTF II di Dago Giri II. Akan tetapi pada saat pembangunan di fase planning belum ditemukannya dokumen kualitas yang bertujuan untuk sebagai landasan kualitas proyek, padahal dokumen kualitas sangat diperlukan untuk melalukan kontrol kualitas pada proyek. Sehingga dirancangnya 100 pernyataan Quality Metric dengan menggunakan metode Internal Control pada beberapa proses aktivitas mulai dari Persiapan, Pengadaan Material, Instalasi, dan Penutupan untuk mengidentifikasi Possible Error dan menghasilkan Critical Success Criteria, serta dibuatnya Resources yang terdiri dari Tools, Man, Material, Method, dan Spesification. Agar pernyataan Quality Metric telah sesuai dengan aktivitas proyek dilakukan penilaian Quality Metric menggunakan perhitungan Skala Guttman berdasarkan penilaian para Project Supervisor, serta belum ditemukannya tools yang dapat mempermudah dalam proses Control Quality terhadap Quality Metric yang telah dirancang sehingga dibuatnya Quality Checklist yang bertujuan untuk membantu perusahaan dalam menstandarisasikan kualitas dari setiap aspek proses aktivitas pada proyek. Kata Kunci : STTF II Dago Giri II, Control Quality, Quality Metric, Quality Checklist, Internal Control, Skala Guttman Abstract PT. XYZ has a STTF II development project in Dago Giri II. However, during the development phase in the planning phase, quality documents were not yet found to be the basis for project quality, even though quality documents were needed to pass quality control on the project. So that 100 Quality Metric statements have been designed using the Internal Control method in a number of activity processes ranging from Preparation, Procurement of Materials, Installation, and Closing to identify Possible Error and produce Critical Success Criteria, as well as making Resources consisting of Tools, Man, Materials, Methods , and Spesification. In order to ensure that the Quality Metric statement is in accordance with the project activities, a Quality Metric assessment is carried out using a Likert Scale calculation based on the assessment of the Project Supervisors and obtains an overall average value of 86.10% which is categorized to be very amenable according to the Likert Scale calculation interval, and there are no tools that can be found. simplify the Quality Control process for the Quality Metric that has been designed so that a Quality Checklist is created which aims to assist the company in standardizing the quality of every aspect of the activity process on the project. Keywords: STTF II Dago Giri II, Quality Control, Quality Metric, Quality Checklist, Internal Control, Likert Guttman